Cover Image, Volume 113, Number 7, July 2016. Issue 7 (July 2016) - Ren, Yudan; Crump, Colin M.; Mackley, Malcolm M.; Li Puma, Gianluca; Reis, Nuno M.
Abstract : Cover Legend This figure shows an artistic representation of UVC inactivation of virus particles in a plastic fluoropolymer microcapillary film. The plastic microcapillary film has a refractive index similar to water and is very transparent to UVC light, consisting of a number of parallel microcapillaries embedded in a flat film. The inner diameter of the microcapillaries is tuned for rapid efficient UVC inactivation of virus particles in continuous flows. The cover image, by Nuno Miguel Reis et al., is based on the Article Photo inactivation of virus particles in microfluidic capillary systems, DOI:10.1002/bit.25912 .